The Effect of Photodynamic Therapy Applied with Different Photosensitizers on Dentin Hardness in Comparison with Conventional Irrigation - Cihan Küden (Cumhuriyet University, 2022)
Objective: The aim of this study was to examine the effect of photodynamic therapy (PDT) using toluidine blue O (TBO), curcumin (CUR) and methylene blue (MB) photosensitizers on root canal dentin microhardness by comparing it with sodium hypochlorite (NaOCl) + ethylenediamine tetraacetic acid (EDTA). Materials and methods: The root canals of 100 human premolar teeth were shaped by the R25 file (Reciproc; VDW, Munich, Germany). The working length of the teeth was determined by using a #10 K-file, keeping it 1mm shorter than the tooth apex. The R25 file was used to prepare the root canals. After every three pecking motions, irrigation was performed and a total of 10 mm of distilled water was used. The specimens were randomly distributed according to the disinfection method; NaOCl+EDTA, PDT with TBO, PDT with CUR, PDT with MB and distilled water (DS) (n=20). Grooves were prepared on the buccal and lingual surfaces of the prepared teeth, parallel to the long axis of the tooth, without touching the root canals. The roots were divided into two parts by means of a cement spatula placed in these grooves. Root canal dentin microhardness was evaluated by the Vickers test method. Three measurements were made by applying 300 g of force for 15 seconds and the average was calculated. It was recorded as the Vickers hardness value. The data were analyzed by using the one-way ANOVA and Dunnett's post hoc tests (α=0.05). Results: All photosensitizer groups showed significantly higher microhardness value than the groups of DS and NaOCl + EDTA (p0.05). Conclusions: PDT with CUR obtained the highest radicular dentin microhardness.